Quality assessment of smoked "galunggong" (Decapterus macrosoma) from four Quezon City markets - Dizon, Casey Lou Cabang; Benedicto, Ana Marie Q. (2002., 2002)
ABSTRACT Samples of smoked "galunggong" purchased from four different markets were evaluated in terms of appearance, physico-chemical attributes, and microbiological characteristics. This study was done to assess the quality of smoked "galunggong" available in local markets. Three samples were purchased exposed along a busy road. Another sample was bought in a similar environment except that it was displayed packed in polyethylene bag. Printed material was consistently used either as wrapper or lining of the product. All four samples were found to still have their gills and viscera. The raw material used for two samples may be declared stale as indicated by the open belly of the fish. The pH values determined ranged from 5.60 to 6.83, a condition susceptible to rapid microbial growth, and the water activity (Aw) values ranged from 0.852 to 0.948, which correspond to the % NaCl range of 2.912-5.897%. Several sorts of filth that indicate a post-processing mishandling were recovered from the four samples. The sample obtained from the Balintawak Wet and Dry Market generally had the highest microbiological load as a consequent of its high pH and Aw condition. The microbiological content of the four samples fell out of the allowable range. Salmonella were present except in the sample obtained from the Balara Market. Staphylococci spp. were also found to exist at a tolerable level. With these results, the product may be declared spoiled and, therefore, unfit for consumption.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Fish, Smoked